2004
DOI: 10.1007/s00221-003-1659-2
|View full text |Cite
|
Sign up to set email alerts
|

Grasping the meaning of words

Abstract: Action affordances can be activated by non-target objects in the visual field as well as by word labels attached to target objects. These activations have been manifested in interference effects of distractors and words on actions. We examined whether affordances could be activated implicitly by words representing graspable objects that were either large (e.g., APPLE) or small (e.g., GRAPE) relative to the target. Subjects first read a word and then grasped a wooden block. Interference effects of the words aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
157
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(182 citation statements)
references
References 32 publications
20
157
2
3
Order By: Relevance
“…This suggestion is compatible with that of Glover, Rosenbaum, Graham, and Dixon (2004), who made a distinction between planning actions and their on-line control. They proposed that the planning of action is based on a visual representation of an object, and that this representation includes both visual and conceptual information.…”
Section: Introductionsupporting
confidence: 86%
“…This suggestion is compatible with that of Glover, Rosenbaum, Graham, and Dixon (2004), who made a distinction between planning actions and their on-line control. They proposed that the planning of action is based on a visual representation of an object, and that this representation includes both visual and conceptual information.…”
Section: Introductionsupporting
confidence: 86%
“…It has to be noted that the insertion of the word prior to the picture presentation and subsequent target display may have also led to a situation typically observed in a number of dual-task studies examining the role of shared resources in cross-modal tasks using auditory and visual sensory modalities (Glover and Dixon, 2002;Glover et al, 2004;Singhal et al, 2007). These and similar studies typically register interference effects from different modality cues in a situation when the cues are presented in a sequence as the processor attempts to make a selection in a situation when both cues compete for the same resource.…”
Section: Discussionmentioning
confidence: 99%
“…Two major models, the first based on Hebbian learning (Pulvermüller, 1996(Pulvermüller, , 2001(Pulvermüller, , 2005 and the second on the existence of the "mirror neuron system" (Fadiga & Craighero, 2004;Gallese & Lakoff, 2005;Rizzolatti & Arbib, 1998;Rizzolatti et al, 2001), suggest that processing of action words relies on activation of the motor programs used to perform, observe or simulate the actions referred to by words, either because of correlation learning (Pulvermüller, 2005) or because of a predisposition for imitation learning (Rizzolatti & Arbib, 1998). Evidence for such shared representations between word processing and sensory-motor information is provided by a large range of empirical data (Aziz-Zadeh et al, 2006;Boulenger et al, 2006;Boulenger et al, in press;Buccino et al, 2005;Glenberg & Kaschack, 2002;Glover et al, 2004;Hauk et al, 2004;Nazir et al, in press;Oliveri et al, 2004;Pulvermüller et al, 2005ab;Tettamanti et al, 2005;Zwaan & Taylor, 2006;see Fischer & Zwaan, in press, for a recent review). fMRI studies, for instance, have demonstrated somatotopic activation of motor and premotor cortices during processing of words or sentences referring to actions performed with arm, face or leg (AzizZadeh et al, 2006;Hauk et al, 2004;Tettamanti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%